Prasyarat Masyarakat Madani dalam Mewujudkan Supremasi Hukum - Mohammad Taher Azhary (Jurnal Hukum IUS QUIA IUSTUM, 1999)
The Civil Society as a form of a new society has been the "conditio sine qua non" for Indonesia in the New Millenium in order for the nation to reach the material and immaterial welfare. The domination of civilian people having high level of education, devouting, having good personality and capability have been the main characteristics of civil society. The members of such society act as decision makers both for political and social affairs. These aim at the benefit of all